In vivo Environment Swiftly Restricts Human Pancreatic Progenitors Toward Mono-Hormonal Identity via a HNF1A/HNF4A Mechanism - Legøy, Thomas Aga; Mathisen, Andreas F.; Salim, Zaidon; Vethe, Heidrun; Bjørlykke, Yngvild; Abadpour, Shadab; Paulo, Joao A.; Scholz, Hanne; Ræder, Helge; Ghila, Luiza; Chera, Simona (Frontiers in Cell and Developmental Biology, 2020)
Generating insulin-producing beta-cells from human induced pluripotent stem cells is a promising cell replacement therapy aimed at improving or curing certain forms of diabetes. Nevertheless, despite important recent advances, the efficient production of functionally mature β-cells is yet to be achieved, with most current differentiation protocols generating a heterogeneous population comprising of subpopulation of cells expressing different islet hormones, including hybrid polyhormonal entities. A solution to this issue is transplanting end-stages differentiating cells into living hosts, which was demonstrated to majorly improve β-cell maturation. Yet, to date, the cellular and molecular mechanisms underlying the transplanted cells response to the in vivo environment exposure was not yet properly characterized. Here we use global proteomics and large-scale imaging techniques aimed at demultiplexing and filtering cellular processes and molecular signatures modulated by the immediate in vivo effect. We show that in vivo exposure swiftly confines in vitro generated human pancreatic progenitors to single hormone expression. The global proteome landscape of the transplanted cells was closer to the one presented by native human islets, especially in regard to energy metabolism and redox balance. Moreover our study indicates a possible link between these processed and certain epigenetic regulators involved in maintenance and propagation of the islet cells identity. Pathway analysis predicted HNF1A and HNF4A as key regulators controlling the in vivo islet-promoting response, with experimental evidence confirming their involvement in confining islet cell identity. To our knowledge this is the first study demultiplexing the immediate response of the transplanted pancreatic progenitors to in vivo exposure.